The Influence of Marketing Mix on Customer Satisfaction and Loyalty at Daja House Restaurant Lampung Indonesia - Nindya Yuliani Arnis; Dewi Wuisan; Gabriel Kennard Chan; Benny Aristo (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
This study aims to analyze the influence of the marketing mix, consisting of food quality, price, location, and service quality, on customer satisfaction and loyalty at Daja House Restaurant in Bandar Lampung. Data for this study was collected through an online questionnaire with 181 respondents who had visited the restaurant more than three times in the last six months. The analysis method used a quantitative approach with a 5-point Likert scale to measure consumer perceptions of the studied variables. The results indicate that each variable in the marketing mix has a positive and significant effect on customer satisfaction, and customer satisfaction has a direct impact on loyalty. This study emphasizes the importance of a positive consumer experience in creating loyalty, especially in the service industry. Practically, this research provides recommendations for the management of Daja House Restaurant to continue improving food quality, adjusting competitive prices, enhancing the layout and comfort of the environment, and training staff to provide responsive and friendly service. In this way, customer satisfaction and loyalty can be increased, ultimately supporting business sustainability amid intense competition.